What's wrong with John? A randomised controlled trial of Mental Health First Aid (MHFA) training with nursing students - Burns, Sharyn; Crawford, Gemma; Hallett, Jonathan; Hunt, Kristen; Chih, Hui Jun; Tilley, P.J. Matt (BioMed Central Ltd., 2017)
BACKGROUND: The prevalence of mental health problems have been found to be higher among university students compared to their non-student peers. Nursing students in particular face a range of additional stressors which may impact their undergraduate performance and their careers. Mental Health First Aid (MHFA) aims to increase mental health literacy and to reduce stigma and may positively impact on the student population. This paper describes a MHFA randomised controlled trial targeting nursing students at a large Australian university. This study aimed to measure the impact of the MHFA course on mental health literacy, mental health first aid intentions, confidence in helping someone with a mental health problem and stigmatising attitudes including social distance. METHODS: Participants were first year nursing students (n = 181) randomly allocated to the intervention (n = 92) or control (n = 89) group. Intervention group participants received the standardised MHFA course for nursing students. Online self-report questionnaires were completed at three time intervals: baseline (one week prior to the intervention: T1) (n = 140), post intervention (T2) (n = 120), and two months post intervention (T3) (n = 109). Measures included demographics, mental health knowledge, recognition of depression, confidence in helping, mental health first aid intentions and stigmatising attitudes including social distance. Repeated measures ANOVA was computed to measure if the impact of time (T1, T2, T3) and group (intervention and control) on the outcome variables. RESULTS: There was a significant improvement among intervention compared to control group participants across the three time periods for knowledge scores (p < 0.001), confidence in helping (p < 0.001), mental health first aid intentions (p < 0.001), total personal stigma (p < 0.05), personal dangerous/unpredictable stigma (p < 0.05) and social distance (p < 0.05) scores. CONCLUSION: MHFA is useful training to embed in university courses and has the potential to enhance mental health literacy and reduce stigmatising attitudes and social distance. While this course has particular salience for nursing and other health science students, there are broader benefits to the general university population that should be considered and opportunities accordingly explored for all students to complete the course. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12614000861651 . Retrospectively registered 11 August 2014.